Community Structure of Soil Insects in Bagek Kembar Ecotourism Area Sekotong West Lombok - Permatasari, Dian Dwi; Ilhamdi, Moh. Liwa; Santoso, Didik (Jurnal Biologi Tropis, 2024)
Human activity in Bagek Kembar Ecotourism is increasing because it is a tourist destination and is close to residential areas. This activity has an impact on biodiversity, especially soil insects in the area. The aim of this research was to determine the structure of the soil insect community. This research is an exploratory descriptive research. Data collection was carried out 8 times in 2 months. Sampling was carried out at 3 stations, namely station 1 on the main ecotourism route, station 2 in the middle of the ecotourism area, and station 3 in the area near the coastline. Samples were taken using the pitfall trap method at 27 trap points. The research results found that 15 sub orders, 30 families, 40 species consisting of 2,525 individuals were found in Bagek Kembar Ecotourism. Station 1 found (825) individuals, station 2 (835) individuals and station 3 (874) individuals of soil insects. Hymenoptera has the largest proportion (31.2%), and the order Thichoptera has the lowest proportion (0.07%). Soil insect composition at station 1 (34%), station 2 (33%) and station 3 (32%).